A avaliação institucional das escolas técnicas do Centro Estadual de Educação Tecnológica Paula Souza - Silva, Marta Leandro da (2008)
Based on the qualitative research methodology in education, we discuss the institutional assessment on the policies of technological education reform, after LDB 9.394/96, focusing on the Institutional Evaluation System of Technological State Schools (SAI ETES) of Centro Paula Souza in the State of São Paulo (1997-2007). We aimed to analyze the conceptions and proposals of institutional assessment expressed by the legal and institutional discourse of Centro Paula Souza, as well as present the perceptions of educational agents (Directors, Coordinators, Teachers, Administrative technician) about the impact and impasses of such assessment policy in the Technological Schools in the context of democratic administration. It was evidenced that the institutional evaluation is presented in the legal speech as the quality support in the combination of the categories: evaluation, quality, autonomy and as an instrument of control-regulation of the public funding. In the Reform of the Public Apparatus the assessment is presented as a centralizing (and/or recentralizing) instrument of decentralization and exempting the state from responsibilities policies. In the perception of the educational subjects it is necessary to restructure the SAIETE, which emphasizes the results evaluation not considering the process evaluation. Assessment is considered an instrument to regulate public financing, expressed by the linkage among institutional assessment, individual performance assessment and salary bonus system. This assessment system does not consider the impacts of the technological education reform policies, as well as the diversity of pedagogical-organizational structures of agriculture and industrial technical schools, consolidated in different professional areas with different needs and political-pedagogical projects.